Analysis of the Compressive Strength of Concrete from Brick Wall Waste as a Concrete Mixture - Paikun, Paikun; Anugrah Amdani, Selfin; Arie Susanto, Daniel; Saepurrahman, Dewa (ASTONJADRO, 2023)
Every building renovation or building reconstruction often occurs demolition of the wall. The demolition of this wall becomes construction waste therefore it is necessary to experiment with using wall waste to become a productive material. This research is an experiment in making concrete using wall waste. The wall waste used is in the form of rubble from the ruins of a red brick wall. The compression test method refers to the 1974:2011 SNI regulations on concrete. In this test, the focus is on the maximum compressive strength of concrete that can be produced in the sample. Each sample of the test object is divided into three groups, each group has three test objects. The first group is a sample of pure concrete, fine aggregate 100% concrete sand. The second group is a fine aggregate experimental concrete sample containing 25% wall waste, and the third group contains 50% wall waste. The test object is in the form of a concrete cylinder with a diameter of 150 mm and a height of 300 mm. Concrete testing is carried out at the age of 7 days, 14 days, and 28 days. The results of this study provide information that red brick wall waste can be recycled into concrete material so that it does not become construction waste. It is known that the compressive strength of concrete using additional wall waste as fine aggregate meets the requirements of structural concrete quality and can improve the quality of concrete. Furthermore, it is hoped that the wall waste can be reused as an added material to the concrete mixture in building construction activities or other construction using concrete.